Modelling negotiation protocols in a dialectical framework - Stankevicius, Alejandro G. (1999)
It has been shown elsewhere that in order to overcome the limitations identified in monotonic reasoning we require a kind of defeasible reasoning. Moreover, defeasible argumentation is one of several approaches that address the problems faced when we attempt to reason defeasibly. Its main goal is to model the kind of reasoning that a single intelligent agent may need. Despite of the fact that defeasible argumentation has been conceived for the single agent scenario, it is possible to consider certain argumentation process (the dialectical analysis) as a dispute or debate between two parties. The two parties view can lead us to an attractive type of negotiation protocol which is based on a formal theory. In this paper, we exploit this approach by defining a dialectical framework capable of modelling a set of negotiation protocols of this kind. We also discuss how these protocols are affected by the design decisions taken inside the framework.